An Analysis of a Severe Turbulence Event Encountered by an Aircraft over the South China Sea and the Application of Numerical Weather Prediction Models in the Early Alerting of the Event - P. W. Chan; W. K. Wong (Advances in Meteorology)
In the literature, there is rather limited number of accounts of significant turbulence over the South China Sea, which is an area of busy air traffic. The present paper documents the meteorological observations of an aircraft over the seas west of the Philippines on encountering severe turbulence associated with an area of convection. From the valuable flight data available from this aircraft, it is found that, on encountering the significant turbulence, the aircraft experienced increase in wind speed, strong downdraft, high windshear hazard factor, and, most importantly, high level of eddy dissipation rate, which is a measure of turbulence intensity in civil aviation. The application of numerical weather prediction (NWP) models in the forecasting of this severe turbulence case is also studied. It turns out that the cumulonimbus extent and in-cloud turbulence potential products from World Area Forecast System may have some indication of the occurrence of significant turbulence associated with convection in the area concerned. A mesoscale NWP model even forecasts the possibility of moderate-to-severe turbulence about 24 to 27 hours ahead of the event.